(untitled) (Gaceta Técnica, 2019)
At this point, not even for the most skeptical, there must remain any doubt about the emergence of BIM (Building Information Modeling) in the work of the civil engineering profession, whether active or passive, or by the mere fact of have been necessary to the requirements of clients or other professional disciplines. According to the criteria of the connoisseurs, the impact of BIM in the field of those known as professions AEC (for its acronym in English Architecture, Engineering and Construction), is comparable or even much deeper to what took place during the irruption of CAD technologies (Computer Assisted Design) during the 1980s, thanks among other things to the reduction of hardware and software costs